Influence of Antibiotics on the Detection of Bacteria by Culture-Based and Culture-Independent Diagnostic Tests in Patients Hospitalized With Community-Acquired Pneumonia. (10th February 2017) - Harris, Aaron M.; Bramley, Anna M.; Jain, Seema; Arnold, Sandra R.; Ampofo, Krow; Self, Wesley H.; Williams, Derek J.; Anderson, Evan J.; Grijalva, Carlos G.; McCullers, Jonathan A.; Pavia, Andrew T.; Wunderink, Richard G.; et al.
Abstract: Background: Specimens collected after antibiotic exposure may reduce culture-based bacterial detections. The impact on culture-independent diagnostic tests is unclear. We assessed the effect of antibiotic exposure on both of these test results among patients hospitalized with community-acquired pneumonia (CAP). Methods: Culture-based bacterial testing included blood cultures and high-quality sputum or endotracheal tube (ET) aspirates; culture-independent testing included urinary antigen testing (adults) for Streptococcus pneumoniae and Legionella pneumophila and polymerase chain reaction (PCR) on nasopharyngeal and oropharyngeal (NP/OP) swabs for Mycoplasma pneumoniae and Chlamydia pneumoniae . The proportion of bacterial detections was compared between specimens collected before and after either any antibiotic exposure (prehospital and/or inpatient) or only prehospital antibiotics and increasing time after initiation of inpatient antibiotics. Results: Of 4678 CAP patients, 4383 (94%) received antibiotics: 3712 (85%) only inpatient, 642 (15%) both inpatient and prehospital, and 29 (<1%) only prehospital. There were more bacterial detections in specimens collected before antibiotics for blood cultures (5.2% vs 2.6%; P < .01) and sputum/ET cultures (50.0% vs 26.8%; P < .01) but not urine antigen (7.0% vs 5.7%; P = .53) or NP/OP PCR (6.7% vs 5.4%; P = .31). For all diagnostic testing, bacterial detections declined with increasing time between inpatient antibiotic administration and specimen collection. Conclusions: Bacteria were less frequently detected in culture-based tests collected after antibiotics and in culture-independent tests that had longer intervals between antibiotic exposure and specimen collection. Bacterial yield could improve if specimens were collected promptly, preferably before antibiotics, providing data for improved antibiotic selection.